REFORM AGRARIAN IN THE FRAME OF DEMOCRACY - Madiong, Baso (Journal of Humanity, 2013)
Agrarian land Resources and The new man will give the greatest possible benefit for life if the rules can be created that enable the mastery and use fair and equitable. Related to it an important determinant factor is the power which would mandate that power or not the mandate. Observing the course of history the nation shows that the period of pre-colonial, colonial, and a period of independence has not obtained a description of the changes that occur in the pattern of the relationship between man and the land (land) assets, the source of power which determines the pattern of utilization of such assets. Problems encountered in the pre-colonial era was not yet found clear information about the relationship between man and the land (the land) and the holders of power because at that time the community has yet to develop such advanced and notes on their lives is still a little bit. The basic agrarian issue is not immediately due to a natural increase of population. Demographic factors also influence the agrarian issue, but the map is not the determining factor. But a decisive, was agrarian politics embraced the ruling regime.